SIMULATION OF STATE OF HIGH-TEMPERATURE OBJECTS UNDER CONDITIONS OF INCREASED RISK - Moskvina, Svitlana; Belokon, Sergiy (Scientific Works of Vinnytsia National Technical University, 2015)
Simulation of high temperature objects state under the conditions of increased risk. The given paper suggests to use the combination of classic and neuron fuzzy models to increase the efficiency of decision – making during the appearance of highly explosive situations. Unlike the existing models it enables to consider the conditions and characteristic of risk situations on the base of the developed fuzzy rules.